BENTONITE AND PHOSPHORITE PRODUCTION OF ORGANOMINERAL FERTILIZERS BASED ON RAW MATERIALS AND NITROGEN-FIXING MICROORGANISMS ((CD:B:NFM=100:5:(0-4)), (CD:B:PF:NFM=100:5:5:(0-4))). - Voqqosov, Zuxriddin; Ikromova , Maftuna (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. This article deals with production of organomineral fertilizers based on local raw materials cattle dung (cattle). local ores (Kyzilkum phosphorite flour (PF) and Navbahor bentonite) and nitrogen-fixing microorganisms. Based on the experiments. the following results were obtained. During 60 days. the raw materials selected for the experiment were used in optimal proportions: cattle dung: bentonite: nitrogen-fixing microorganisms solution (NFM) (100:5:0-4) and the main chemistry of organomineral fertilizers obtained on the basis of cattle dung. bentonite. phosphorite flour and nitrogen-fixing microorganisms. Composition (CD:B:PF:NFM=100:5:5:(0-4)) was analyzed. Methods. The obtained results from our side were first studied the quantities of organomineral fertilizers based on cattle dung. bentonite and nitrogen-fixing microorganisms. Cattle dung. bentonite and nitrogen-fixing microorganisms of the type Azotobacterium were used for laboratory research. For this. cattle dung: bentonite ratios were taken in the range of 100:(2.5-5) and the resulting mixture was processed with nitrogen-fixing microorganisms (NFM) grown in Fedorov medium in the ratio of 100:(2.5-5):(0.5-4.0).